Analisis Penerapan Peraturan OJK Nomor 35/PJOK 05/2018 Pada Pembiayaan Channeling di BPRS Riyal Irsyadi terhadap Koperasi Karyawan PT. Bakrie Autoparts - Muhammad Asyraf Anshari; Eva Misfah Bayuni; Intan Manggala Wijayanti (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Channeling pattern where the position of the Cooperative as a liaison between the Bank and the members of the Cooperative. The liaison in this broad sense, namely assisting the Bank in all its activities, starting from selecting prospective customers, selecting good customer characteristics, helping to draw up agreements and the use of finances. In carrying out its function as an intermediation institution, namely expanding its financing to the economic sector and MSMEs, BPRS Riyal Irsyadi carries out Linkage program cooperation with BMT MFIs and KSPPS Cooperatives and Employee Cooperatives. The purpose of this study is to examine the conformity of the chaneling financing pattern scheme implemented by BPRS Riyal Irsyadi with OJK regulation Number 35 / PJOK 05/2018, this research uses qualitative research methods with descriptive methods, The results of this study the implementation of Channeling Financing run by BPRS Riyal Irsyadi must be guided by POJK No. 35 / POJK.05 / 2018, because this basis is an absolute thing carried out by BPRS as a guideline in carrying out these financing activities. In addition, the implementation of channeling financing at BPRS Riyal Irsyadi with the Employee Cooperative of PT Bakrie Autoparts that the financing activity is very beneficial for each party. And Analysis of the Application of POJK No.35 / POJK.05 / 2018 on Channeling Financing at BPRS Riyal Irsyadi with employee cooperatives PT Bakrie Autoparts the implementation of financing has not been fully in accordance with POJK No.35 / POJK.05 / 2018. Abstrak. Pola Channeling dimana kedudukan Koperasi sebagai penghubung antara Bank dengan anggota Koperasi. Penghubung pada dalam arti luas ini, yaitu membantu Bank pada seluruh kegiatannya, mulai dari pemilihan calon nasabah, menseleksi ciri nasabah yang baik, membantu menyusun perjanjian serta penggunaan keuangannya. Dalam menjalankan fungsinya sebagai lembaga intermediasi, yakni memperluas pembiayaannya kepada sektor- sektor ekonomis dan UMKM, BPRS Riyal Irsyadi menjalankan kerjasama Linkage program dengan LKMS BMT dan Koperasi KSPPS maupun Koperasi Karyawan. Tujuan dari penelitian ini adalah untuk meneliti terkait keseuaian skema pola pembiayaan chaneling yang dilaksanakan oleh BPRS Riyal Irsyadi dengan peraturan OJK Nomor 35/ PJOK 05/2018, penelitian ini menggunakan metode penelitian kualitatif dengan metode deskriptif, hasil penelitian ini Pelaksanaan Pembiayaan Channeling yang dijalankan oleh BPRS Riyal Irsyadi harus berpedoman pada POJK No. 35/POJK.05/2018, karena dasar tersebut menjadi hal yang mutlak dijalankan oleh BPRS sebagai pedoman dalam melaksanakan kegiatan pembiayaan tersebut. Selain itu Pelaksanaan Pembiayaan Channeling di BPRS Riyal Irsyadi dengan Koperasi Karyawan PT Bakrie Autoparts bahwa kegiatan pembiayaan tersebut sangat besar manfaatnya bagi masing- masing Pihak. Dan Analisis Penerapan POJK No.35/POJK.05/2018 pada Pembiayaan Channeling di BPRS Riyal Irsyadi dengan Koperasi karyawan PT Bakrie Autoparts pelaksanaan pembiayaannya belum sepenuhnya sesuai dengan POJK No.35/POJK.05/2018.